Literature review: The role of learning management system (LMS) in improving the digital literacy of educators - Gunawan, Rahmat Dwi; Sutisna, Anan; Ana, Elsa Fitri (Universitas Negeri Yogyakarta, 2024)
This literature review is conducted based on an empirical phenomenon that describes the use of technology in the education sector due to the demands of increasingly advanced developments. It aims to explain the role of using a learning management system (LMS) in increasing the digital literacy level of educators who use LMS to support the learning process. It adopted the PRISMA analysis technique. The results of the literature review show that efforts to increase educators' digital literacy may come from their own will (internal) or others' encouragement or help (external). In addition, the learning management system in the learning process may also be one way to increase educators' digital literacy through the intense interaction between educators and using the learning management system.